2000
DOI: 10.1001/jama.284.10.1256
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hospital Teaching Status With Quality of Care and Mortality for Medicare Patients With Acute MI

Abstract: In this study of elderly patients with AMI, admission to a teaching hospital was associated with better quality of care based on 3 of 4 quality indicators and lower mortality. JAMA. 2000;284:1256-1262

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
189
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(204 citation statements)
references
References 50 publications
11
189
1
3
Order By: Relevance
“…13 Teaching status and its relationship to quality of care and outcomes have been examined across illnesses and procedures. 14 Many of these studies suggest that teaching hospitals have more favorable clinical outcomes. Levels of expertise and staffing may be an underlying explanation for the observed volume-outcome link; this could be modified to improve outcomes in low-volume hospitals.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…13 Teaching status and its relationship to quality of care and outcomes have been examined across illnesses and procedures. 14 Many of these studies suggest that teaching hospitals have more favorable clinical outcomes. Levels of expertise and staffing may be an underlying explanation for the observed volume-outcome link; this could be modified to improve outcomes in low-volume hospitals.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…[1][2][3][4] Previously published reports have found that, despite substantial differences in case mix, being admitted to a teaching hospital is associated with reduced morbidity and risk-adjusted mortality for various conditions compared with receiving care delivered at a nonacademic hospital. 2,[5][6][7][8][9][10][11][12][13] For example, among 248 major teaching, minor teaching, and nonteaching hospitals in New York state, Polanczyk et al found that major teaching hospital status was an important determinant of outcomes in patients hospitalized with myocardial infarction, heart failure, or stroke. 1 Some studies have noted that the high cost of care at teaching hospitals may offset these potential benefits.…”
mentioning
confidence: 99%
“…Allison and colleagues demonstrated an improved quality of care and lower mortality rate in patients treated at major academic institutions after acute myocardial infarction. 19 Similarly, Polanczyk and colleagues found lower heart failure, myocardial infarction and stroke-adjusted mortality rates in major academic institutions. 21 These findings are highly valuable given that several authors have questioned the overall value of academic institutions and impact of academic affiliation on rc outcomes support continued investment in funds required to run these institutions.…”
Section: Discussionmentioning
confidence: 93%
“…For example, higher quality of care measures, [18][19][20] and lower complication and mortality rates 18,19,[21][22][23][24] were observed in patients treated at academic institutions. On the other hand, others have also reported no difference or worse outcomes at academic institutions.…”
Section: Discussionmentioning
confidence: 99%